2009
DOI: 10.1111/j.1365-2753.2009.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhospital management of COPD exacerbations: a systematic review of the literature with regard to adherence to international guidelines

Abstract: Rationale Chronic obstructive pulmonary disease (COPD) exacerbations are a leading cause of hospitalization. Suboptimal inhospital management is expected to lead to more frequent exacerbations and recurrent hospital admission, and is associated with increased mortality. Aims To explore inhospital management of COPD and to compare the results with recommendations from international guidelines. Methods A literature search was carried out for relevant articles published 2000-2009 in the databases Medline, Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 56 publications
5
55
1
Order By: Relevance
“…On a patient level, health-related quality of life remains substantially impaired across all spirometric stages, adherence across multiple aspects of therapy (including smoking cessation, physical exercise and activity, and maintenance medications) remains disappointingly low [1], and only about 40% become successful self-managers despite educational efforts [2,3]. On a health care provider level, comorbidities -which often contribute substantially to total disease burden [4] -are frequently underestimated or even ignored [5], adherence to practice guidelines for COPD is suboptimal [6,7], and referral to standard-of-care pulmonary rehabilitation is unacceptably low [1]. On a system level, COPD remains a leading cause of mortality, and health care utilization, as reflected by a 30-day hospital readmission rate hovering around 20% [8][9][10], remains unacceptably high.…”
Section: Introductionmentioning
confidence: 99%
“…On a patient level, health-related quality of life remains substantially impaired across all spirometric stages, adherence across multiple aspects of therapy (including smoking cessation, physical exercise and activity, and maintenance medications) remains disappointingly low [1], and only about 40% become successful self-managers despite educational efforts [2,3]. On a health care provider level, comorbidities -which often contribute substantially to total disease burden [4] -are frequently underestimated or even ignored [5], adherence to practice guidelines for COPD is suboptimal [6,7], and referral to standard-of-care pulmonary rehabilitation is unacceptably low [1]. On a system level, COPD remains a leading cause of mortality, and health care utilization, as reflected by a 30-day hospital readmission rate hovering around 20% [8][9][10], remains unacceptably high.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of literature addressing adherence to the GOLD guidelines, by Lodewijckx and colleagues, found that spirometry was performed in only 12% to 18% of COPD patients hospitalized with COPD exacerbations. 22 It would appear that clinicians have either not read the guidelines, are following the ATS/ERS recommendations, or are skeptical of the value of spirometry in these patients altogether.…”
Section: What Is the Role Of Spirometry And D Lco In Hospitalized Patmentioning
confidence: 99%
“…4,5 DSTs often improve adherence to published guidelines and in many instances improve clinical outcomes, although this has not been universally true. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, most research on clinical decision support has focused upon patient management after initial assessment and diagnosis or through mandatory alerts for providers, such as reminders for intraoperative antibiotic prophylaxis, postoperative nausea and vomiting prophylaxis, or proper use of alarms for separate from cardiopulmonary bypass. [26][27][28][29][30][31][32][33][34] In contrast, the use of DSTs for patient assessment/diagnosis and the subsequent application of evidence-based protocols has yet to be rigorously tested.…”
Section: Introductionmentioning
confidence: 99%